Geochemical Investigation of Organic Matter of Riphean Deposit Rocks of the Ust'-Mayskaya Well (Aldan Anteclise); AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Krasnoyarova N. A. Nataliya Alekseevna (2018, 2018)
Title screen